Polyimide resin, polyimide varnish and polyimide film
By using the combination of specific structural units A and B, the generated polyimide resin forms a polyimide film, solving the problem that polyimide films are difficult to achieve high thermal stability, elongation and transparency in the prior art, and achieving a high-performance film material suitable for display substrate.
Patent Information
- Application Number
- JP2021574671
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2021-01-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-01-20
AI Technical Summary
When used in liquid crystal displays or OLED displays, it is difficult to achieve high thermal stability and good extension at the same time, while maintaining transparency and colorlessness.
Using a combination of specific structural units A and B, the structural unit A is derived from norbornane-2-spiro-α-cyclopentanone-α'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride, and the structural unit B is derived from 2,2'-bis(trifluoromyl)-4,4'-diaminodiphenyl ether. The polyimide resin generated by the reaction is formed to form a polyimide film.
The polyimide film maintains good elongation and color lessness transparency under high heat conditions, and is suitable for substrate of liquid crystal displays and OLED displays.
Smart Images

Figure 0007647589000001 
Figure 0007647589000002 
Figure 0007647589000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyimide resin, a polyimide varnish, and a polyimide film. [Background technology]
[0002] Polyimide resins have excellent mechanical properties, and various applications in the fields of electrical and electronic components are being considered. For example, it is desirable to replace glass substrates used in image display devices such as liquid crystal displays and OLED displays with plastic substrates in order to make the devices lighter and more flexible, and research into polyimide resins suitable as such plastic materials is also being conducted. High transparency is also required for such applications.
[0003] For example, Patent Document 1 discloses a polyimide and its precursor that contain repeating units derived from norbornane-2-spiro-α-cyclopentanone-α'-spiro-2″-norbornane-5,5″,6,6″-tetracarboxylic acids as a raw material, and have a linear thermal expansion coefficient of 100 ppm / K or less at 50 to 400° C., with the aim of achieving high transparency, bending resistance, high heat resistance, and a low linear thermal expansion coefficient. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-066017 A Summary of the Invention [Problem to be solved by the invention]
[0005] When a polyimide film substrate is used as an image display device such as a liquid crystal display or an OLED display, the substrate must be heat resistant, especially in the process of forming a polysilicon film on the substrate. In recent years, polyimide films are also required to have elongation, which is an index of toughness, in order to realize thinner and more flexible devices. However, films with excellent heat resistance are hard and have poor elongation. Furthermore, for display applications, not only the transparency but also colorlessness is becoming more important. As described above, there has been a demand for a polyimide resin capable of producing a polyimide film that is excellent in both heat resistance and elongation, and is also colorless and transparent. An object of the present invention is to provide a polyimide resin which has both heat resistance and elongation and is also excellent in colorless transparency. [Means for solving the problem]
[0006] The present inventors discovered that a polyimide resin containing a specific combination of structural units can solve the above problems, and thus completed the invention.
[0007] That is, the present invention relates to the following [1] to [8]. [1] A polyimide resin comprising a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, wherein the structural unit A comprises a structural unit (A1) derived from a compound represented by the following formula (a1), and the structural unit B comprises a structural unit (B1) derived from a compound represented by the following formula (b1):
[0008] [ka]
[0009] [2] The polyimide resin according to the above [1], wherein the structural unit A further contains a structural unit (A2), and the structural unit (A2) is at least one selected from the group consisting of a structural unit (A21) derived from a compound represented by the following formula (a21), a structural unit (A22) derived from a compound represented by the following formula (a22), and a structural unit (A23) derived from a compound represented by the following formula (a23):
[0010] [ka]
[0011] [3] The polyimide resin according to the above [1] or [2], wherein the structural unit B further contains a structural unit (B2), and the structural unit (B2) is at least one selected from the group consisting of a structural unit (B21) derived from a compound represented by the following formula (b21) and a structural unit (B22) derived from a compound represented by the following formula (b22):
[0012] [ka] [4] The polyimide resin according to any one of the above [1] to [3], wherein the structural unit B further contains a structural unit (B2), and the structural unit (B2) contains a structural unit (B22) derived from a compound represented by the following formula (b22): [ka] [5] The polyimide resin according to any one of the above [1] to [4], wherein the structural unit A further contains a structural unit (A2), and the structural unit (A2) contains a structural unit (A22) derived from a compound represented by the following formula (a22): [ka]
[0013] [6] A polyimide varnish obtained by dissolving the polyimide resin according to any one of the above [1] to [5] in an organic solvent. [7] A polyimide film comprising the polyimide resin according to any one of the above [1] to [5]. [8] A method for producing a polyimide film, comprising applying or forming the polyimide varnish according to [6] above into a film, and then removing the organic solvent. Effect of the Invention
[0014] The polyimide resin of the present invention is compatible with heat resistance and elongation, and further has excellent colorless transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] [Polyimide resin] The polyimide resin of the present invention is a polyimide resin containing a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, in which the structural unit A contains a structural unit (A1) derived from a compound represented by the following formula (a1), and the structural unit B contains a structural unit (B1) derived from a compound represented by the following formula (b1).
[0016] [ka]
[0017] The reason why the polyimide resin of the present invention, which contains the structural units (A1) and (B1), can achieve both heat resistance and elongation and also has excellent colorless transparency is not clear, but it is thought to be due to a combined effect resulting from the rigidity and randomness of the molecular chain due to the norbornane skeleton, ether bond, etc.
[0018] <Constituent unit A> The structural unit A is a structural unit derived from a tetracarboxylic dianhydride, and contains a structural unit (A1) derived from a compound represented by formula (a1). The structural unit (A1) improves heat resistance, elongation, and colorless transparency, and in particular improves heat resistance and colorless transparency.
[0019] The compound represented by formula (a1) is norbornane-2-spiro-α-cyclopentanone-α'-spiro-2″-norbornane-5,5″,6,6″-tetracarboxylic acid dianhydride.
[0020] The structural unit A may contain a structural unit other than the structural unit (A1). The structural unit A preferably further contains a structural unit (A2) in addition to the structural unit (A1). The structural unit (A2) is a structural unit derived from a compound represented by the following formula (a2). The structural unit (A2) improves elongation in particular, and also improves mechanical properties such as strength.
[0021] [ka]
[0022] In formula (a2), L is a single bond or a divalent linking group. The divalent linking group is preferably a substituted or unsubstituted alkylene group, more preferably -CR 1 R 2 - (where R 1 and R 2 are each independently a hydrogen atom or a substituted or unsubstituted alkyl group, or R 1 and R 2 are bonded to each other to form a ring. L is preferably one selected from the group consisting of a single bond, a group represented by the following formula (L1) and a group represented by the following formula (L2), in which * indicates a bonding site to an aromatic ring.
[0023] [ka]
[0024] The structural unit (A2) is preferably at least one selected from the group consisting of a structural unit (A21) derived from a compound represented by the following formula (a21), a structural unit (A22) derived from a compound represented by the following formula (a22), and a structural unit (A23) derived from a compound represented by the following formula (a23), and is preferably at least one selected from the group consisting of a structural unit (A21) derived from a compound represented by the following formula (a21), and a structural unit (A22) derived from a compound represented by the following formula (a22). From the viewpoint of improving elongation, it is more preferably the structural unit (A21) derived from a compound represented by the following formula (a21), and from the viewpoint of heat resistance, it is more preferably the structural unit (A22) derived from a compound represented by the following formula (a22). That is, it is more preferable that the structural unit A further contains a structural unit (A2), and that the structural unit (A2) further contains a structural unit (A21) derived from a compound represented by the following formula (a21), and it is more preferable that the structural unit A further contains a structural unit (A2), and that the structural unit (A2) further contains a structural unit (A22) derived from a compound represented by the following formula (a22).
[0025] [ka]
[0026] The compound represented by formula (a21) is biphenyltetracarboxylic dianhydride (BPDA), and specific examples thereof include 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA) represented by formula (a21s) below, 2,3,3',4'-biphenyltetracarboxylic dianhydride (a-BPDA) represented by formula (a21a) below, and 2,2',3,3'-biphenyltetracarboxylic dianhydride (i-BPDA) represented by formula (a21i) below.
[0027] [ka]
[0028] The compound represented by the formula (a22) is 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride. The compound represented by formula (a23) is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.
[0029] The content ratio of the structural unit (A1) in the structural unit A is preferably 50 mol% or more, more preferably 55 mol% or more, even more preferably 60 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, and even more preferably 95 mol% or more. The upper limit of the content ratio of the structural unit (A1) is not particularly limited, that is, it is 100 mol%. The structural unit A may be composed only of the structural unit (A1). By including the structural unit (A1) in the structural unit A in the above content ratio, the colorless transparency and heat resistance are particularly excellent.
[0030] When the structural unit A contains the structural unit (A2), the proportion of the structural unit (A2) in the structural unit A is preferably 5 to 50 mol %, more preferably 10 to 40 mol %, and even more preferably 15 to 35 mol %. When the structural unit A contains the structural unit (A2), the molar ratio of the structural unit (A1) to the structural unit (A2) [(A1) / (A2)] is preferably 50 / 50 to 95 / 5, more preferably 60 / 40 to 90 / 10, and even more preferably 65 / 35 to 85 / 15. By containing the structural unit (A2) in the structural unit A in the above content ratio, the mechanical properties, particularly elongation, strength, and the like, are excellent.
[0031] The structural unit A may contain structural units other than the structural units (A1) and (A2). The tetracarboxylic dianhydride forming such a structural unit is not particularly limited, but may include aromatic tetracarboxylic dianhydrides such as pyromellitic dianhydride (excluding the compound represented by formula (a2)); alicyclic tetracarboxylic dianhydrides such as 1,2,3,4-cyclobutane tetracarboxylic dianhydride and 1,2,4,5-cyclohexane tetracarboxylic dianhydride (excluding the compound represented by formula (a1)); and aliphatic tetracarboxylic dianhydrides such as 1,2,3,4-butane tetracarboxylic dianhydride. In this specification, the term "aromatic tetracarboxylic acid dianhydride" refers to a tetracarboxylic acid dianhydride containing one or more aromatic rings, the term "alicyclic tetracarboxylic acid dianhydride" refers to a tetracarboxylic acid dianhydride containing one or more alicyclic rings but no aromatic rings, and the term "aliphatic tetracarboxylic acid dianhydride" refers to a tetracarboxylic acid dianhydride containing neither an aromatic ring nor an alicyclic ring. The structural unit other than the structural unit (A1) optionally contained in the structural unit A may be of one type, or of two or more types.
[0032] <Structural unit B> The structural unit B is a structural unit derived from a diamine, and contains a structural unit (B1) derived from a compound represented by formula (b1). The structural unit (B1) improves heat resistance, elongation, and colorless transparency, and in particular improves elongation and colorlessness.
[0033] The compound represented by formula (b1) is 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether (6FODA).
[0034] The structural unit B may contain a structural unit other than the structural unit (B1). The structural unit B preferably further contains a structural unit (B2) in addition to the structural unit (B1). The structural unit (B2) is preferably at least one selected from the group consisting of a structural unit (B21) derived from a compound represented by the following formula (b21) and a structural unit (B22) derived from a compound represented by the following formula (b22). The structural unit (B2) improves heat resistance in particular, and also improves the elastic modulus. From the viewpoint of improving transparency, dimensional stability against heat, and elastic modulus, the structural unit (B2) is preferably a structural unit (B22) derived from a compound represented by formula (b22). That is, it is preferable that the structural unit B further contains a structural unit (B2), and the structural unit (B2) contains a structural unit (B22) derived from a compound represented by the following formula (b22). Furthermore, the structural unit (B2) is preferably a structural unit (B21) derived from a compound represented by formula (b21), and the structural unit (B21) particularly improves the heat resistance and elastic modulus.
[0035] [ka]
[0036] The compound represented by formula (b21) is 9,9-bis(4-aminophenyl)fluorene. The compound represented by formula (b22) is 2,2'-bis(trifluoromethyl)benzidine.
[0037] The content ratio of the structural unit (B1) in the structural unit B is preferably 10 mol% or more, more preferably 20 mol% or more, even more preferably 30 mol% or more, even more preferably 50 mol% or more, even more preferably 60 mol% or more, and even more preferably 80 mol% or more. The upper limit of the content ratio of the structural unit (B1) is not particularly limited, that is, it is 100 mol%. The structural unit B may be composed only of the structural unit (B1). By including the structural unit (B1) in the structural unit B in the above content ratio, the elongation is particularly improved, and the colorlessness is also improved.
[0038] When the structural unit B contains the structural unit (B2), the ratio of the structural unit (B2) in the structural unit B is preferably 1 to 90 mol %, more preferably 1 to 80 mol %, even more preferably 2 to 70 mol %, still more preferably 3 to 50 mol %, even more preferably 4 to 40 mol %, and even more preferably 5 to 20 mol %. When the structural unit B contains the structural unit (B2), particularly from the viewpoints of colorlessness, elongation, and transparency, the molar ratio of the structural unit (B1) to the structural unit (B2) [(B1) / (B2)] is preferably 10 / 90 to 99 / 1, more preferably 20 / 80 to 99 / 1, even more preferably 30 / 70 to 98 / 2, still more preferably 50 / 50 to 97 / 3, still more preferably 60 / 40 to 96 / 4, and even more preferably 80 / 20 to 95 / 5. Furthermore, from the standpoint of improving mechanical properties such as elastic modulus, heat resistance, and thermal properties such as dimensional stability against heat, the molar ratio of the structural unit (B1) to the structural unit (B2) [(B1) / (B2)] is preferably 10 / 90 to 60 / 40, more preferably 10 / 90 to 50 / 50, even more preferably 10 / 90 to 40 / 60, still more preferably 10 / 90 to 30 / 70, still more preferably 10 / 90 to 20 / 80, and even more preferably 10 / 90 to 15 / 85.
[0039] When the structural unit B contains the structural unit (B2) and the structural unit (B2) contains the structural unit (B22), particularly from the viewpoints of colorlessness, elongation, and transparency, the molar ratio of the structural unit (B1) to the structural unit (B22) [(B1) / (B22)] is preferably 10 / 90 to 99 / 1, more preferably 20 / 80 to 99 / 1, even more preferably 30 / 70 to 98 / 2, still more preferably 50 / 50 to 97 / 3, still more preferably 60 / 40 to 96 / 4, and even more preferably 80 / 20 to 95 / 5. Furthermore, from the standpoint of improving mechanical properties such as elastic modulus, heat resistance, and thermal properties such as dimensional stability against heat, the molar ratio of the structural unit (B1) to the structural unit (B22) [(B1) / (B22)] is preferably 10 / 90 to 60 / 40, more preferably 10 / 90 to 50 / 50, even more preferably 10 / 90 to 40 / 60, still more preferably 10 / 90 to 30 / 70, still more preferably 10 / 90 to 20 / 80, and even more preferably 10 / 90 to 15 / 85.
[0040] The structural unit B may contain a structural unit other than the structural units (B1) and (B2). The diamine forming such a structural unit is not particularly limited, but may be 1,4-phenylenediamine, p-xylylenediamine, 3,5-diaminobenzoic acid, 2,2'-dimethylbiphenyl-4,4'-diamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)hexafluoropropane, bis(4-aminophenyl)sulfone, 4,4'-diaminobenzanilide, 1-(4-aminophenyl)-2,3-dihydro-1,3,3-trimethyl-1H-inden-5-amine, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, 1,4-dimethyl ... aromatic diamines such as 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane (excluding the compounds represented by formula (b1), (b21), and (b22)); alicyclic diamines such as 1,3-bis(aminomethyl)cyclohexane and 1,4-bis(aminomethyl)cyclohexane; and aliphatic diamines such as ethylenediamine and hexamethylenediamine. In this specification, an aromatic diamine refers to a diamine containing one or more aromatic rings, an alicyclic diamine refers to a diamine containing one or more alicyclic rings but no aromatic rings, and an aliphatic diamine refers to a diamine containing neither an aromatic ring nor an alicyclic ring. The structural unit other than the structural unit (B1) optionally contained in the structural unit B may be of one type, or of two or more types.
[0041] <Characteristics of polyimide resin> From the viewpoint of the mechanical strength of the resulting polyimide film, the number average molecular weight of the polyimide resin of the present invention is preferably 5,000 to 200,000. The number average molecular weight of the polyimide resin can be determined, for example, from a standard polymethyl methacrylate (PMMA)-equivalent value measured by gel filtration chromatography.
[0042] The polyimide resin of the present invention has both heat resistance and elongation, and is also excellent in colorless transparency, and can have the following physical properties.
[0043] The polyimide resin of the present invention, when made into a polyimide film having a thickness of 10 μm, has a total light transmittance of preferably 85% or more, more preferably 88% or more, even more preferably 90% or more, and still more preferably 91% or more.
[0044] The polyimide resin of the present invention, when formed into a polyimide film having a thickness of 10 μm, preferably has a yellow index (YI) of 3.5 or less, more preferably 3.0 or less, and even more preferably 2.0 or less.
[0045] The glass transition temperature (Tg) of the polyimide resin of the present invention is preferably 350° C. or higher, more preferably 380° C. or higher, even more preferably 400° C. or higher, and still more preferably 430° C. or higher. The total light transmittance, yellow index (YI) and glass transition temperature (Tg) in the present invention can be specifically measured by the methods described in the examples.
[0046] [Manufacturing method of polyimide resin] The polyimide resin of the present invention can be produced by reacting a tetracarboxylic acid component containing a compound that provides the above-mentioned structural unit (A1) with a diamine component containing a compound that provides the above-mentioned structural unit (B1).
[0047] Compounds that provide the structural unit (A1) include, but are not limited to, compounds represented by formula (a1), and may be derivatives thereof as long as they can form the same structural unit. Such derivatives include tetracarboxylic acids corresponding to the compound represented by formula (a1) (i.e., norbornane-2-spiro-α-cyclopentanone-α'-spiro-2″-norbornane-5,5″,6,6″-tetracarboxylic acid) and alkyl esters of the tetracarboxylic acids. Compounds that provide the structural unit (A1) are preferably compounds represented by formula (a1) (i.e., tetracarboxylic dianhydrides).
[0048] The tetracarboxylic acid component may contain a compound other than the compound that provides the structural unit (A1). The tetracarboxylic acid component preferably contains, in addition to the compound that provides the structural unit (A1), a compound that provides the structural unit (A2). Compounds that provide the structural unit (A2) include, but are not limited to, compounds represented by formula (a2), and may be derivatives thereof as long as they can form the same structural unit. Examples of such derivatives include tetracarboxylic acids corresponding to the compounds represented by formula (a2) and alkyl esters of the tetracarboxylic acids. Compounds that provide the structural unit (A2) are preferably compounds represented by formula (a2) (i.e., tetracarboxylic dianhydrides). The compound that provides the structural unit (A2) is preferably at least one selected from the group consisting of compounds that provide the structural unit (A21) represented by formula (a21), compounds that provide the structural unit (A22) represented by formula (a22), and compounds that provide the structural unit (A23) represented by formula (a23), and is preferably at least one selected from the group consisting of compounds that provide the structural unit (A21) and compounds that provide the structural unit (A22). From the viewpoint of improving elongation, it is more preferably a compound that provides the structural unit (A21), and from the viewpoint of heat resistance, it is more preferably a compound that provides the structural unit (A22).
[0049] The tetracarboxylic acid component preferably contains 50 mol% or more of the compound that gives the structural unit (A1), more preferably 55 mol% or more, even more preferably 60 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, and even more preferably 95 mol% or more. The upper limit of the content of the compound that gives the structural unit (A1) is not particularly limited, that is, it is 100 mol%. The tetracarboxylic acid component may be composed of only the compound that gives the structural unit (A1).
[0050] When the tetracarboxylic acid component contains a compound that provides the structural unit (A2), the tetracarboxylic acid component preferably contains 5 to 50 mol %, more preferably 10 to 40 mol %, and even more preferably 15 to 35 mol % of the compound that provides the structural unit (A2). When the tetracarboxylic acid component contains a compound that provides the structural unit (A2), the molar ratio of the compound that provides the structural unit (A1) to the compound that provides the structural unit (A2) [(A1) / (A2)] is preferably 50 / 50 to 95 / 5, more preferably 60 / 40 to 90 / 10, and even more preferably 65 / 35 to 85 / 15.
[0051] The tetracarboxylic acid component may contain a compound other than the compound that provides the structural unit (A1) and the compound that provides the structural unit (A2). Examples of such compounds include the above-mentioned aromatic tetracarboxylic acid dianhydrides, alicyclic tetracarboxylic acid dianhydrides, and aliphatic tetracarboxylic acid dianhydrides, as well as derivatives thereof (tetracarboxylic acids, alkyl esters of tetracarboxylic acids, etc.). The compound optionally contained in the tetracarboxylic acid component (that is, a compound other than the compound that provides the structural unit (A1)) may be one type, or two or more types.
[0052] The compound that gives the structural unit (B1) may be a compound represented by formula (b1), but is not limited thereto, and may be a derivative thereof as long as it can form the same structural unit. The derivative may be a diisocyanate corresponding to the compound represented by formula (b1). The compound that gives the structural unit (B1) is preferably a compound represented by formula (b1) (i.e., a diamine).
[0053] The diamine component may contain a compound other than the compound that provides the structural unit (B1). The diamine component preferably contains, in addition to the compound that provides the structural unit (B1), a compound that provides the structural unit (B2). From the viewpoints of improving transparency, dimensional stability against heat, and elastic modulus, the compound that provides the structural unit (B2) is preferably a compound that provides the structural unit (B22) represented by formula (b22), and from the viewpoints of improving heat resistance and elastic modulus, the structural unit (B2) is preferably a compound that provides the structural unit (B21) represented by formula (b21). Compounds that provide the structural unit (B2) include, but are not limited to, compounds represented by formula (b21) and compounds represented by formula (b22), and may be derivatives thereof as long as they can form the same structural unit. Examples of such derivatives include diisocyanates corresponding to the compound represented by formula (b21) and diisocyanates corresponding to the compound represented by formula (b22). Compounds that provide the structural unit (B2) are preferably compounds represented by formula (b21) and compounds represented by formula (b22) (i.e., diamines).
[0054] The diamine component preferably contains 10 mol% or more of the compound that gives the structural unit (B1), more preferably 20 mol% or more, even more preferably 30 mol% or more, even more preferably 50 mol% or more, even more preferably 60 mol% or more, and even more preferably 80 mol% or more. The upper limit of the content ratio of the compound that gives the structural unit (B1) is not particularly limited, that is, it is 100 mol%. The diamine component may be composed of only the compound that gives the structural unit (B1).
[0055] When the diamine component contains a compound that provides the structural unit (B2), the diamine component contains the compound that provides the structural unit (B2) in an amount of preferably 1 to 90 mol %, more preferably 1 to 80 mol %, even more preferably 2 to 70 mol %, still more preferably 3 to 50 mol %, even more preferably 4 to 40 mol %, and even more preferably 5 to 20 mol %. When the diamine component contains a compound that provides the structural unit (B2), particularly from the viewpoints of colorlessness, elongation, and transparency, the molar ratio of the compound that provides the structural unit (B1) to the compound that provides the structural unit (B2) [(B1) / (B2)] is preferably 10 / 90 to 99 / 1, more preferably 20 / 80 to 99 / 1, even more preferably 30 / 70 to 98 / 2, still more preferably 50 / 50 to 97 / 3, still more preferably 60 / 40 to 96 / 4, and even more preferably 80 / 20 to 95 / 5. Furthermore, from the standpoint of improving mechanical properties such as elastic modulus, heat resistance, and thermal properties such as dimensional stability against heat, the molar ratio of the compound providing structural unit (B1) to the compound providing structural unit (B2) [(B1) / (B2)] is preferably 10 / 90 to 60 / 40, more preferably 10 / 90 to 50 / 50, even more preferably 10 / 90 to 40 / 60, still more preferably 10 / 90 to 30 / 70, still more preferably 10 / 90 to 20 / 80, and even more preferably 10 / 90 to 15 / 85.
[0056] When the diamine component contains a compound that provides the structural unit (B2), and the compound that provides the structural unit (B2) contains a compound that provides the structural unit (B22), particularly from the viewpoints of colorlessness, elongation, and transparency, the molar ratio of the compound that provides the structural unit (B1) to the compound that provides the structural unit (B22) [(B1) / (B22)] is preferably 10 / 90 to 99 / 1, more preferably 20 / 80 to 99 / 1, even more preferably 30 / 70 to 98 / 2, still more preferably 50 / 50 to 97 / 3, even more preferably 60 / 40 to 96 / 4, and even more preferably 80 / 20 to 95 / 5. Furthermore, from the standpoint of improving mechanical properties such as elastic modulus, heat resistance, and thermal properties such as dimensional stability against heat, the molar ratio of the compound providing structural unit (B1) to the compound providing structural unit (B22) [(B1) / (B22)] is preferably 10 / 90 to 60 / 40, more preferably 10 / 90 to 50 / 50, even more preferably 10 / 90 to 40 / 60, still more preferably 10 / 90 to 30 / 70, still more preferably 10 / 90 to 20 / 80, and even more preferably 10 / 90 to 15 / 85.
[0057] The diamine component may contain a compound other than the compound that provides the structural unit (B1) and the compound that provides the structural unit (B2). Examples of such compounds include the above-mentioned aromatic diamines, alicyclic diamines, and aliphatic diamines, as well as their derivatives (diisocyanates, etc.). The compound optionally contained in the diamine component (that is, a compound other than the compound that provides the structural unit (B1)) may be one type, or two or more types.
[0058] In the present invention, the ratio of the amounts of the tetracarboxylic acid component and the diamine component used in the production of the polyimide resin is preferably 0.9 to 1.1 mol of the diamine component per 1 mol of the tetracarboxylic acid component.
[0059] In the present invention, in addition to the above-mentioned tetracarboxylic acid component and diamine component, a terminal blocking agent may be used in the production of the polyimide resin. As the terminal blocking agent, monoamines or dicarboxylic acids are preferred. The amount of the terminal blocking agent to be introduced is preferably 0.0001 to 0.1 moles per mole of the tetracarboxylic acid component, and particularly preferably 0.001 to 0.06 moles. As the monoamine terminal blocking agent, for example, methylamine, ethylamine, propylamine, butylamine, benzylamine, 4-methylbenzylamine, 4-ethylbenzylamine, 4-dodecylbenzylamine, 3-methylbenzylamine, 3-ethylbenzylamine, aniline, 3-methylaniline, 4-methylaniline, etc. are recommended. Among these, benzylamine and aniline are preferably used. As the dicarboxylic acid terminal blocking agent, dicarboxylic acids are preferred, and a part of them may be ring-closed. For example, phthalic acid, phthalic anhydride, 4-chlorophthalic acid, tetrafluorophthalic acid, 2,3-benzophenonedicarboxylic acid, 3,4-benzophenonedicarboxylic acid, cyclohexane-1,2-dicarboxylic acid, cyclopentane-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, etc. are recommended. Of these, phthalic acid and phthalic anhydride are preferably used.
[0060] The method for reacting the tetracarboxylic acid component and the diamine component is not particularly limited, and any known method can be used. Specific reaction methods include (1) a method in which a tetracarboxylic acid component, a diamine component, and a reaction solvent are charged into a reactor, and the mixture is stirred at 0 to 80°C for 0.5 to 30 hours, and then the temperature is raised to carry out the imidization reaction; (2) a method in which a diamine component and a reaction solvent are charged into a reactor and dissolved, and then the tetracarboxylic acid component is charged, and the mixture is stirred at 0 to 80°C for 0.5 to 30 hours as necessary, and then the temperature is raised to carry out the imidization reaction; and (3) a method in which a tetracarboxylic acid component, a diamine component, and a reaction solvent are charged into a reactor, and the temperature is immediately raised to carry out the imidization reaction.
[0061] The reaction solvent used in the production of the polyimide resin may be any solvent that does not inhibit the imidization reaction and can dissolve the resulting polyimide. Examples of the solvent include aprotic solvents, phenolic solvents, ether solvents, and carbonate solvents.
[0062] Specific examples of aprotic solvents include amide-based solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-methylcaprolactam, 1,3-dimethylimidazolidinone, and tetramethylurea; lactone-based solvents such as γ-butyrolactone and γ-valerolactone; phosphorus-containing amide-based solvents such as hexamethylphosphoric amide and hexamethylphosphine triamide; sulfur-containing solvents such as dimethyl sulfone, dimethyl sulfoxide, and sulfolane; ketone-based solvents such as acetone, cyclohexanone, and methylcyclohexanone; amine-based solvents such as picoline and pyridine; and ester-based solvents such as 2-methoxy-1-methylethyl acetate.
[0063] Specific examples of phenol-based solvents include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, and 3,5-xylenol. Specific examples of ether solvents include 1,2-dimethoxyethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, bis[2-(2-methoxyethoxy)ethyl]ether, tetrahydrofuran, and 1,4-dioxane. Specific examples of carbonate solvents include diethyl carbonate, methyl ethyl carbonate, ethylene carbonate, and propylene carbonate. Among the above reaction solvents, amide-based solvents and lactone-based solvents are preferred. The above reaction solvents may be used alone or in combination of two or more.
[0064] In the imidization reaction, it is preferable to carry out the reaction while removing water generated during the production using a Dean-Stark apparatus, etc. By carrying out such an operation, it is possible to further increase the degree of polymerization and the imidization rate.
[0065] In the above imidization reaction, a known imidization catalyst can be used, such as a base catalyst or an acid catalyst. Examples of the base catalyst include organic base catalysts such as pyridine, quinoline, isoquinoline, α-picoline, β-picoline, 2,4-lutidine, 2,6-lutidine, trimethylamine, triethylamine, tripropylamine, tributylamine, triethylenediamine, imidazole, N,N-dimethylaniline, and N,N-diethylaniline; and inorganic base catalysts such as potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogencarbonate, and sodium hydrogencarbonate. Examples of the acid catalyst include crotonic acid, acrylic acid, trans-3-hexenoic acid, cinnamic acid, benzoic acid, methylbenzoic acid, oxybenzoic acid, terephthalic acid, benzenesulfonic acid, paratoluenesulfonic acid, naphthalenesulfonic acid, etc. The above imidization catalysts may be used alone or in combination of two or more kinds. Among the above, from the viewpoint of handleability, it is preferable to use a base catalyst, more preferably an organic base catalyst, further preferably triethylamine, and particularly preferably a combination of triethylamine and triethylenediamine.
[0066] The temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C., from the viewpoints of reaction rate and suppression of gelation, etc. The reaction time is preferably 0.5 to 10 hours after the start of distillation of the produced water.
[0067] [Polyimide varnish] The polyimide varnish of the present invention is obtained by dissolving the polyimide resin of the present invention in an organic solvent. That is, the polyimide varnish of the present invention contains the polyimide resin of the present invention and an organic solvent, and the polyimide resin is dissolved in the organic solvent. The organic solvent is not particularly limited as long as it dissolves the polyimide resin. However, it is preferable to use the above-mentioned compounds as reaction solvents used in the production of the polyimide resin, either alone or in combination of two or more kinds. Since the polyimide resin of the present invention has solvent solubility, it can be made into a highly concentrated varnish that is stable at room temperature. The polyimide varnish of the present invention preferably contains 3 to 40 mass % of the polyimide resin of the present invention, more preferably 5 to 30 mass %. The viscosity of the polyimide varnish is preferably 0.1 to 200 Pa·s, more preferably 0.5 to 150 Pa·s. In addition, the polyimide varnish of the present invention may contain various additives such as inorganic fillers, adhesion promoters, release agents, flame retardants, UV stabilizers, surfactants, leveling agents, defoamers, fluorescent brightening agents, crosslinking agents, polymerization initiators, and photosensitizers, as long as the additives do not impair the required properties of the polyimide film. The method for producing the polyimide varnish of the present invention is not particularly limited, and any known method can be applied.
[0068] [Polyimide film and method for producing polyimide film] The polyimide film of the present invention contains the polyimide resin of the present invention, and therefore has good heat resistance and elongation, and is also excellent in colorless transparency. The method for producing the polyimide film of the present invention (production method) is not particularly limited, and known methods can be used. For example, the polyimide varnish of the present invention is applied or molded into a film, and then the organic solvent is removed. From the viewpoint of obtaining a smooth film with a desired thickness, the method for removing the organic solvent after applying or molding the polyimide varnish of the present invention into a film is preferred.
[0069] The polyimide film of the present invention has good heat resistance and elongation, and is also excellent in colorless transparency, and is therefore suitable for use as a film for various components such as color filters, flexible displays, semiconductor parts, optical components, etc. The polyimide film of the present invention is particularly suitable for use as a substrate for image display devices such as liquid crystal displays and OLED displays. EXAMPLES
[0070] The present invention will be described in detail below with reference to examples, although the present invention is not limited to these examples in any way. The solids concentration of the varnishes and the physical properties of the polyimide films obtained in the Examples and Comparative Examples were measured by the methods described below. The results are shown in Table 1.
[0071] (1) Solid content concentration The solids concentration of the varnish was measured by heating the sample at 320°C for 120 min in a small electric furnace "MMF-1" manufactured by AS ONE Corporation, and calculating from the mass difference of the sample before and after heating. (2) Film thickness The film thickness was measured using a micrometer manufactured by Mitutoyo Corporation. (3) Total light transmittance, yellow index (YI) The measurements were performed in accordance with JIS K7361-1 using a color and turbidity simultaneous measuring device "COH400" manufactured by Nippon Denshoku Industries Co., Ltd. (4) Haze The measurements were performed in accordance with JIS K7361-1 using a color and turbidity simultaneous measuring device "COH7700" manufactured by Nippon Denshoku Industries Co., Ltd. (5) Glass transition temperature (Tg) Using a thermomechanical analyzer "TMA / SS6100" manufactured by Hitachi High-Tech Science Corporation, the sample was heated to above Tg in tensile mode under conditions of a sample size of 2mm x 20mm, a load of 0.1N, and a heating rate of 10℃ / min to remove residual stress. Then, TMA measurement was performed under the same conditions from 50℃ to 500℃ to determine Tg. (6) Coefficient of linear thermal expansion (CTE) Using a thermomechanical analyzer "TMA / SS6100" manufactured by Hitachi High-Tech Science Corporation, TMA measurements were performed in tensile mode under conditions of a sample size of 2 mm x 20 mm, a load of 0.1 N, and a heating rate of 10°C / min, and the CTE from 100 to 350°C was calculated. (7)1% weight loss temperature (Td1%) A Hitachi High-Tech Science Corporation differential thermal and thermogravimetric simultaneous analyzer "TG / DTA6200" was used. The sample was heated from 40 to 550°C at a heating rate of 10°C / min, and the temperature at which the weight was reduced by 1% compared to the weight at 300°C was defined as the 1% weight loss temperature. The higher the weight loss temperature, the better. (8) Elastic modulus and strength The elastic modulus and strength are tensile modulus and tensile strength in accordance with JIS K7127, and were measured using a tensile tester "Strograph VG-1E" manufactured by Toyo Seiki Co., Ltd. (9) Elongation The elongation was measured by a tensile test (measurement of elongation percentage) in accordance with JIS K 7127. Test pieces having a width of 10 mm and a thickness of 10 to 60 μm were used.
[0072] The tetracarboxylic acid components and diamine components used in the examples and comparative examples, as well as their abbreviations, are as follows: <Tetracarboxylic acid component> CpODA: norbornane-2-spiro-α-cyclopentanone-α'-spiro-2″-norbornane-5,5″,6,6″-tetracarboxylic dianhydride (manufactured by JX Nippon Oil & Energy Corporation; compound represented by formula (a1)) s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride (compound represented by formula (a21s)) BPAF: 9,9'-bis(3,4-dicarboxyphenyl)fluorene dianhydride (manufactured by JFE Chemical Corporation; compound represented by formula (a22)) TAHQ: p-phenylenebis(trimellitate)dianhydride (manufactured by Manac Corporation) <Diamine component> 6FODA: 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether (manufactured by ChinaTech (Tianjin) Chemical Co., Ltd., a compound represented by formula (b1)) BAFL: 9,9-bis(4-aminophenyl)fluorene (manufactured by Taoka Chemical Co., Ltd.; compound represented by formula (b21)) TFMB: 2,2'-bis(trifluoromethyl)benzidine (manufactured by Wakayama Seika Kogyo Co., Ltd.; compound represented by formula (b22))
[0073] The abbreviations for the solvents and imidization catalysts used in the examples and comparative examples are as follows. NMP: N-methyl-2-pyrrolidone (manufactured by Mitsubishi Chemical Corporation) GBL: γ-butyrolactone (manufactured by Mitsubishi Chemical Corporation) TEDA: Triethylenediamine TEA: Triethylamine
[0074] <Example 1> 33.624 g (0.100 mol) of 6FODA and 86.474 g of GBL were added to a 500 mL five-neck round-bottom flask equipped with a stainless steel half-moon shaped stirring blade, a nitrogen inlet tube, a Dean-Stark condenser, a thermometer, and a glass end cap, and the mixture was stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 70°C to obtain a solution. To this solution, 38.438g (0.100 mol) of CpODA and 21.619g of GBL were added all at once, and then the imidization catalyst, 0.506g of TEA, and 0.056g of TEDA were added, and the reaction system was heated with a mantle heater, and the temperature in the reaction system was raised to 190°C over about 20 minutes. The components that were distilled off were collected, and the temperature in the reaction system was maintained at 190°C and refluxed for about 5 hours while adjusting the rotation speed according to the increase in viscosity. Thereafter, 279.836 g of GBL was added so that the solid content concentration was 15% by mass, and the temperature inside the reaction system was cooled to 100° C., after which the mixture was further stirred for about 1 hour for homogenization, to obtain a polyimide varnish. The resulting polyimide varnish was then applied onto a glass plate by spin coating, held on a hot plate at 80°C for 20 minutes, and then heated in a hot air dryer at 400°C for 30 minutes under a nitrogen atmosphere (heating rate: 5°C / min) to evaporate the solvent and obtain a film.
[0075] <Example 2> A polyimide varnish was prepared in the same manner as in Example 1, except that the amount of CpODA was changed from 38.438 g (0.100 mol) to 30.750 g (0.080 mol) and 5.884 g (0.020 mol) of s-BPDA was added, to obtain a polyimide varnish with a solid content concentration of 15 mass%. A film was obtained in the same manner as in Example 1 using the obtained polyimide varnish.
[0076] <Example 3> A polyimide varnish was prepared in the same manner as in Example 1, except that the amount of 6FODA was changed from 33.624 g (0.100 mol) to 3.362 g (0.010 mol) and 28.822 g (0.090 mol) of TFMB was added, to obtain a polyimide varnish with a solids concentration of 15 mass%. A film was obtained in the same manner as in Example 1 using the obtained polyimide varnish.
[0077] <Example 4> A polyimide varnish was prepared in the same manner as in Example 1, except that the amount of 6FODA was changed from 33.624 g (0.100 mol) to 6.725 g (0.020 mol) and 25.619 g (0.080 mol) of TFMB was added, to obtain a polyimide varnish with a solids concentration of 15 mass%. A film was obtained in the same manner as in Example 1 using the obtained polyimide varnish.
[0078] <Example 5> A polyimide varnish was prepared in the same manner as in Example 1, except that the amount of 6FODA was changed from 33.624 g (0.100 mol) to 16.812 g (0.050 mol) and 16.012 g (0.050 mol) of TFMB was added, to obtain a polyimide varnish with a solids concentration of 15 mass%. A film was obtained in the same manner as in Example 1 using the obtained polyimide varnish.
[0079] <Example 6> A polyimide varnish was prepared in the same manner as in Example 1, except that the amount of 6FODA was changed from 33.624 g (0.100 mol) to 20.174 g (0.060 mol) and 13.938 g (0.040 mol) of BAFL was added, and the amount of CpODA was changed from 38.438 g (0.100 mol) to 23.063 g (0.060 mol) and 11.769 g (0.040 mol) of s-BPDA was added. A polyimide varnish with a solids concentration of 15 mass% was obtained. A film was obtained in the same manner as in Example 1 using the obtained polyimide varnish.
[0080] <Example 7> A polyimide varnish was prepared in the same manner as in Example 1, except that the amount of 6FODA was changed from 33.624 g (0.100 mol) to 18.493 g (0.055 mol) and 15.680 g (0.045 mol) of BAFL was added, and the amount of CpODA was changed from 38.438 g (0.100 mol) to 34.594 g (0.090 mol) and 4.584 g (0.010 mol) of BPAF was added. A polyimide varnish with a solids concentration of 15 mass% was obtained. A film was obtained in the same manner as in Example 1 using the obtained polyimide varnish.
[0081] <Comparative Example 1> 32.024 g (0.100 mol) of TFMB and 84.554 g of GBL were added to a 500 mL five-neck round-bottom flask equipped with a stainless steel half-moon shaped stirring blade, a nitrogen inlet tube, a Dean-Stark condenser, a thermometer, and a glass end cap, and the mixture was stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 70°C to obtain a solution. To this solution, 38.438g (0.100 mol) of CpODA and 21.139g of GBL were added all at once, and then 0.506g of TEA and 0.056g of TEDA were added as imidization catalysts, and the reaction system was heated with a mantle heater and the temperature in the reaction system was raised to 190°C over about 20 minutes. The components that were distilled off were collected, and the temperature in the reaction system was maintained at 190°C and refluxed for about 5 hours while adjusting the rotation speed according to the increase in viscosity. Then, 273.169 g of GBL was added so that the solid concentration was 15% by mass, and the temperature in the reaction system was cooled to 100° C., after which the mixture was further stirred for about 1 hour to homogenize, and a cloudy (hazy) polyimide varnish was obtained. After 24 hours, the varnish had gelled and lost its fluidity, making it difficult to form a film, and no film was obtained.
[0082] <Comparative Example 2> 33.624 g (0.100 mol) of 6FODA and 201.747 g of NMP were placed in a 500 mL five-neck round-bottom flask equipped with a stainless steel half-moon shaped stirring blade, a nitrogen inlet tube, a Dean-Stark equipped cooling tube, a thermometer, and a glass end cap, and the mixture was stirred at 200 rpm under a nitrogen atmosphere at an internal temperature of 50°C to obtain a solution. To this solution, 29.422 g (0.100 mol) of s-BPDA and 50.437 g of NMP were added all at once, and the mixture was stirred for 5 hours while being maintained at 50° C. by a mantle heater. Thereafter, 105.077 g of NMP was added and homogenized, and then the mixture was cooled to room temperature to obtain a polyamic acid varnish having a solid content concentration of 15 mass %. The resulting polyamic acid varnish was then spin-coated onto a glass plate and held at 80°C for 20 minutes on a hot plate, after which it was heated at 400°C for 30 minutes in a hot air dryer under a nitrogen atmosphere (heating rate: 5°C / min) to evaporate the solvent and further thermally imidize to obtain a polyimide film.
[0083] <Comparative Example 3> A polyamic acid varnish having a solid content concentration of 15 mass % was produced in the same manner as in Comparative Example 2, except that 38.438 g (0.100 mol) of CpODA was changed to 45.833 g (0.100 mol) of TAHQ. A polyimide film was obtained in the same manner as in Comparative Example 2 using the obtained polyamic acid varnish.
[0084] [Table 1]
[0085] As shown in Table 1, the polyimide films of the examples are excellent in both heat resistance and elongation, and further, are excellent in colorless transparency.
Claims
1. A polyimide resin comprising a structural unit A derived from a tetracarboxylic dianhydride and a structural unit B derived from a diamine, The structural unit A includes a structural unit (A1) derived from a compound represented by the following formula (a1): The structural unit B includes a structural unit (B1) derived from a compound represented by the following formula (b1): A polyimide resin in which the structural unit A further contains a structural unit (A2), and the structural unit (A2) is at least one selected from the group consisting of a structural unit (A21) derived from a compound represented by the following formula (a21), a structural unit (A22) derived from a compound represented by the following formula (a22), and a structural unit (A23) derived from a compound represented by the following formula (a23): 【Chemistry 1】 【Chemistry 2】
2. 2. The polyimide resin according to claim 1, wherein the structural unit B further comprises a structural unit (B2), and the structural unit (B2) is at least one selected from the group consisting of a structural unit (B21) derived from a compound represented by the following formula (b21) and a structural unit (B22) derived from a compound represented by the following formula (b22): 【Chemistry 3】
3. 3. The polyimide resin according to claim 1 or 2, wherein the structural unit B further comprises a structural unit (B2), and the structural unit (B2) comprises a structural unit (B22) derived from a compound represented by the following formula (b22): 【Chemistry 4】
4. The polyimide resin according to any one of claims 1 to 3, wherein the structural unit A further comprises a structural unit (A2), and the structural unit (A2) comprises a structural unit (A22) derived from a compound represented by the following formula (a22): 【Chemistry 5】
5. A polyimide varnish obtained by dissolving the polyimide resin according to any one of claims 1 to 4 in an organic solvent.
6. A polyimide film comprising the polyimide resin according to any one of claims 1 to 4.
7. A method for producing a polyimide film, comprising applying or forming the polyimide varnish according to claim 5 into a film and then removing the organic solvent.
Citation Information
Patent Citations
Polyimide production method and polyimide obtained by the same
JP2015108092A
Polyimide precursor and polyimide
JP2018066017A
Polyamic acid solution and transparent polyimide resin film based on the same
JP2019112632A
Method for manufacturing transparent heat-resistant layered film, transparent heat-resistant layered film, flexible printed circuit board, substrate for flexible display, front plate for flexible display, LED illumination device, and organic electroluminescence display device
WO2016129329A1
Polyimide resin
WO2017191822A1